Four essays in behavioural finance and experimental economics - Khan, Tanvir Nabi (2020)
The PhD thesis consists of 4 separate but related pieces of works. All of them are associated with various behavioural phenomena that can affect the way individuals or a group of individuals make economic decisions. The PhD thesis adopts two methods of research: empirical and experimental.